Advanced Computational Intelligence Paradigms in Healthcare-2 - Vaidya, S.; Jain, L. C.; Yoshida, H.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2007)
Computational intelligence paradigms offer many advantages in maintaining and enhancing the field of healthcare. This volume presents seven chapters selected from the rapidly growing application areas of computational intelligence to healthcare systems, including intelligent synthetic characters, man-machine interface, menu generators, analysis of user acceptance, pictures archiving and communication systems. This book will serve as a useful resource for the health professionals, professors, students, and the computer scientists, who are working on or interested in learning healthcare systems, to overview the current stat-of-the-art of diverse applications of computational intelligence to healthcare practice. .
to Computational Intelligence in Healthcare -- Synthetic Characters in Health-related Applications -- Application of Artificial Intelligence for Weekly Dietary Menu Planning -- Evaluation of Healthcare IT Applications: The User Acceptance Perspective -- Current Perspectives on PACS and a Cardiology Case Study -- Attacking the Inverse Electromagnetic Problem of the Heart with Computationally Compatible Anatomical and Histological Knowledge -- Human Machine Interface for Healthcare and Rehabilitation.
Keywords: Engineering; Artificial intelligence; Applied mathematics; Engineering mathematics; Engineering; Appl.Mathematics/Computational Methods of Engineering; Artificial Intelligence (incl. Robotics).; Electronic books